A Predatory Crime: Drug Facilitated Sexual Assaults and Perpetrator Typology - Fırat, Sunay; Erk, Mehmet Aykut (The Bulletin of Legal Medicine, 2019)
Drug Facilitated Sexual Assault (DFSA) is a type of sexual assault which occurs when victim is vulnerable to perpetrator’s attack due to sedation and hypnotic effects of the higher amount of consumption of alcohol and/or another psychoactive drug. By its very nature of sexual assault, DFSA has to be taken carefully after the victim restores his/her consciousness.The aim is to contribute to the Crime and Behavioral Sciences, penological interventions and rehabilitation attempts by examining how the perpetrators’ risk factors, possible mental or personality disorders in their developmental history and perpetrators’ characteristics affect the sexual offenses based on recent literature.The perpetrator of DFSA can be a person that has any other psychopathological history. However, according to some research results perpetrator may portray different characteristics for each case. Even if the perpetrator of DFSA acknowledges the behavior of himself/herself, he/she does not give any moral reaction to alleged behavior. DFSA requires high knowledge of behavioral sciences and toxicology. Those requirements of perpetrator help him/her by making victims unconsciousness and let him/her get what he/she desires. After all the victim may or may not realize what does happen to him/her.To sum up it is important to have a firm definition of DFSA in order to approach profoundly to those incidents. An extensive definition will be useful for the latter researches. Due to the fact that Turkey has not got any Sexual Assault Crises Center in a modern meaning, the medical, psycho-social and legal aid which victim needs cannot be given.
Keywords: Drug Facilitated Sexual Assault; Perpetrator Typology; Modus Operandi